Performance Evaluation of Coconut Wood Veneer Composite for Sustainable Construction Material - Shamil Haque Kizhakkethodi Mansoor; Vishnu Raju; Anish Mavila Chathoth; Shibu Comath; Adiyodi Venugopal Santhoshkumar; Sreejith Babu; Pavin Praize Sunny; Arjun Memuttathu Sajeevan (BioResources)
The abundant coconut palm (Cocos nucifera L.) offers an appealing alternative to meet the increasing demand for wood panels, providing both functional and aesthetic benefits. However, the sclerenchymatous vascular bundle of coconut wood poses challenges for rotary peeling, and the high capital and operational costs associated with palm wood limit its practical use. Consequently, this preliminary study aimed to develop pure and hybrid coconut-sawn veneer composites (using Macaranga peltata). Veneers were bonded with phenol-formaldehyde resin in crossband orientation and hot-pressed (40 kg/cm², 135 to 140 °C, 15 min). Four types of 3-layer composites were produced: Pure medium-density coconut composite (Pure-MD), Pure high-density coconut composite (Pure-HD), coconut-Macaranga hybrid medium-density composite (Hybrid-MoD), and coconut-Macaranga hybrid high-density composite (Hybrid-HD). Physico-mechanical tests revealed that Pure-MD and Pure-HD met Indian standards (IS 303:1989), demonstrating good strength and stiffness. In contrast, high-density composites showed reduced glue adhesion. Hybrid-MD satisfied most criteria except bending stress, restricting high-load applications. Hybrid-HD failed in internal bonding and bending, limiting its utility. The study highlights the potential of pure coconut composites under optimized conditions. However, further improvements are needed for high-density and hybrid composites, focusing on adhesive type, surface modification, veneer alignment, and hot-pressing parameters.